A strategic and tactical approach to global business ethics - Beer, Lawrence A. (International business collection., 2015)
The inclusion of ethically driven elements into the strategic planning process of multinational corporations (MNCs) is an emerging consideration in the modern era of globalization. Firms pursuing cross-border activities in any capacity and to whatever degree or scale are increasingly coming into contact with differences in morally applied decision making that affects their operational success and sustainability. The choices made require the use of clear and unambiguous codes of conduct for embedded managers abroad. The implementation of a properly administered code, coupled with a program of corporate social responsibility (CSR), can add value to a company, while its misapplication or exclusion can diminish value.